Desenvolvimento de sementes de Sesbania virgata (Cav.) Pres. - Teixeira, Fabrício Palla (2016)
There are large amount of studies exploring diverse aspects related with agronomic seeds, however there is a lack of information about the forest seeds. Sesbania virgata is a tree species from the Fabaceae family and, due to its fast development and rusticity, among other factors, is normally used on reforestation programs, being the seedlings produced mostly from seeds. Thus, studies related to S. virgata seed biology are important as background for its propagation and conservation. This study addressed the morphological, physiological and molecular aspects of the desiccation tolerance acquisition on S. virgata seeds during the maturation process. After marking flowers on field, were collected fruits on different maturation stages for the desiccation tolerance acquisition tests, involving the physical characterization of fruits and seeds, microscopy, histochemical studies and the electrophoretic profile of total and heat resistant proteins. The seeds reached the highest fresh mass at 44 days after the anthesis (DAA). At 85 DAA, seeds are completely mature, with an average of 6.3% of water content. It was also possible to observe the lignin deposition at the end of the maturation and protein accumulation. The desiccation tolerance was observed at 44 DAA, however, only was observed normal seedlings formation after 75 DAA. In the firsts stages was not observed protein accumulation, but after 32 DAA was initiated the synthesis of both total and heat resistant proteins, being constant in its abundance until the end of the maturation. These results allowed to characterize the seed development and the desiccation tolerance of S. virgata.